Realization of the Right to Health Protection in Insurance Medicine: The First Experience of Covid-19 - Луцюк, Павло Сергійович; Луцюк, П. С.; Луцюк, Павел Сергеевич; Lutsiuk, Pavlo S.; Lutsyuk, Pavlo; Болокан, Інна Вікторівна; Болокан, І. В.; Болокан, Инна Викторовна; Bolokan, Inna V.; Давидова, Ірина Віталіївна; Давидова, І. В.; Давыдова, Ирина Витальевна; et al. (Los Hemisferios University, 2020)
This article analyze the effectiveness of insurance medicine and the negative consequences of its work, which we could observe in the first period of the pandemic. The research methodology is based on general and special scientific methods, in particular: formal-legal, historical-legal, comparative analysis, and modeling. The procedure and issues to be considered are as follows: in the introduction, we will consider the concept of “the right to health care” and why it is important; in the first section, we will look at the general state of affairs, figures for different countries, and the first results of the fight against the pandemic; in the second section, we will touch on some of the problems of access to health care in the insurance system and its aggravation in connection with the pandemic; in the third, we will consider the impact of the pandemic on the health insurance system and how it could have been avoided some problems. The results of this study emphasize that the medical insurance system has extremely unsatisfactorily coped with the pandemic and its consequences, and therefore it is necessary at least to carry out a full-fledged official, and at best to develop an urgent comprehensive modernization program, taking into account the above positive experience of other developed countries.

У цій статті проаналізовано ефективність страхової медицини та негативні наслідки її роботи, які ми могли спостерігати в перший період пандемії. Методологія дослідження базується на загальних та спеціальних наукових методах, зокрема: формально-правовому, історико-правовому, порівняльному аналізі та моделюванні. Процедура та питання, які слід розглянути, такі: у вступі ми розглянемо поняття «право на охорону здоров’я» та чому це важливо; у першому розділі ми розглянемо загальний стан справ, цифри для різних країн та перші результати боротьби з пандемією; у другому розділі ми торкнемося деяких проблем доступу до медичної допомоги в системі страхування та її загострення у зв'язку з пандемією; у третьому - ми розглянемо вплив пандемії на систему медичного страхування та те, як можна було уникнути деяких проблем. Результати цього дослідження підкреслюють, що система медичного страхування вкрай незадовільно впоралася з пандемією та її наслідками, і тому необхідно хоча б виконувати повноцінну державну, а в кращому випадку - розробити термінову комплексну програму модернізації, беручи до уваги та враховуючи вищезазначений позитивний досвід інших розвинених країн.

В этой статье проанализирована эффективность страховой медицины и негативные последствия ее работы, которые мы могли наблюдать в первый период пандемии. Методология исследования базируется на общих и специальных научных методах, в частности: формально-правовом, историко-правовом, сравнительном анализе и моделировании. Процедура и вопросы, которые следует рассмотреть, следующие: во введении мы рассмотрим понятие «право на охрану здоровья» и почему это важно; в первой главе мы рассмотрим общее состояние дел, цифры для разных стран и первые результаты борьбы с пандемией; во второй главе мы коснемся некоторых проблем доступа к медицинской помощи в системе страхования и ее обострение в связи с пандемией; в третьей - мы рассмотрим влияние пандемии на систему медицинского страхования и то, как можно было избежать некоторых проблем. Результаты этого исследования подчеркивают, что система медицинского страхования крайне неудовлетворительно справилась с пандемией и ее последствиями, и поэтому необходимо хотя бы выполнять полноценную государственную, а в лучшем случае - разработать срочную комплексную программу модернизации, учитывая вышеупомянутый положительный опыт других развитых стран.
Lutsyuk P. Realization of the Right to Health Protection in Insurance Medicine: The First Experience of Covid-19 / P. Lutsyuk, I. Bolokan, I. Davydova, A. Chanysheva, S. Yakymchuk // Ius Humani. Law Journal. – V. 9 (2). – Los Hemisferios University, 2020. – P. 341-364.
Keywords: right to health; coronavirus; health care system; public medicine; private medicine; право на здоров'я; коронавірус; система охорони здоров'я; державна медицина; приватна медицина; право на здоровье; коронавирус; система здравоохранения; государственная медицина; частная медицина; Research Subject Categories::LAW/JURISPRUDENCE